2008
DOI: 10.1007/s10453-008-9099-x
|View full text |Cite
|
Sign up to set email alerts
|

Short-term dynamic patterns of bioaerosol generation and displacement in an indoor environment

Abstract: The short-term dynamics and distribution of airborne biological and total particles have been assessed in a large university hallway by particle counting using laser particle counters and impaction air samplers. Particle numbers of four different size ranges were determined every 2 min over several hours. Bioaerosols (culturable bacteria and fungi determined as colony-forming units) were directly collected every 5 min on Petri dishes containing the appropriate growth medium. Results clearly show distinct short… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 19 publications
(25 reference statements)
2
17
0
Order By: Relevance
“…The number of culturable fungi correlated well with total number of particles <2.5 m [6]. However, other studies showed that also bacterial numbers are only correlated to size rages of 1 to 5 m and >5 m [56].…”
Section: Particle Countingmentioning
confidence: 71%
See 3 more Smart Citations
“…The number of culturable fungi correlated well with total number of particles <2.5 m [6]. However, other studies showed that also bacterial numbers are only correlated to size rages of 1 to 5 m and >5 m [56].…”
Section: Particle Countingmentioning
confidence: 71%
“…1 to 5 m) and the number of fungal or bacterial colony forming units [55][56][57][58]. Particle counting can be done on a fast basis (using appropriate equipment) without the need of applying air sampling and microbial identification techniques (e.g.…”
Section: Particle Countingmentioning
confidence: 99%
See 2 more Smart Citations
“…Long-term exposure to indoor environments with inadequate air exchange and poor air quality may cause sick building syndrome (SBS), allergic reactions, respiratory tract infection, and lung cancer (Dales et al, 2008;Joshi, 2008;Sidra et al, 2015). Bioaerosols are suspended biological particles consisting of microorganisms or organism-derived materials (Douwes et al, 2003;Brandl et al, 2008). Indoor airborne biological pollutants have numerous sources, including outdoor air, human bodies, wallpaper, carpet, resuspended particles, air conditioning systems, and animal waste (Lindemann et al, 1982;Pastuszka et al, 2000;Chao et al, 2002;Hargreaves et al, 2003;Kalogerakis et al, 2005;Tseng et al, 2011;Hospodsky et al, 2012;Xu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%